THE QUEST OF DEVELOPING A BETTER ENGLISH TRAINING MATERIAL FOR MIGRANT WORKER CANDIDATES IN INDONESIA - Desi Nahartini; Ratna Sari Dewi; Siti Fitriah; Maya Defianty; Zaharil Anasy (University of Kuningan, 2021)
The scarcity of job opportunities in Indonesia has encouraged some of its citizen to work abroad; these workers are commonly known as PMI (Pekerja Migran Indonesia –Indonesian migrant workers). One of the salient challenges encountered by PMI occupied in the semi-skilled and unskilled employment, which shared the highest percentage of PMI, is limited English proficiency. This has caused a range of formidable impacts ranging from misunderstandings between the employer and PMI to making PMI less preferable compare to workers from other countries. This research aims to (1) evaluate materials used in the English training programs by BLKLN (Balai Latihan Kerja Luar Negeri -Overseas Training Centre for Indonesian Migrant Workers); (2) Identify PMI’s perceptions concerning their English language needs. Forty-five PMI in Malaysia and Thirty-Six PMI in Singapore were involved in this case study research. Findings from the study revealed that there are gaps between how English is taught at BLKLN and PMI’s language learning needs to the extent of materials and method. Hence, findings from this research put an urgent call to improvement in the English language training at BLKLN in order to meet the PMI’s learning needs.